Nitroxyl (azanone) trapping by metalloporphyrins - Doctorovich, Fabio (2011)
The present review starts describing nitroxyl (azanone, 1HNO) biological relevance, in relation with NO physiology, from a chemical reactivity perspective. After a description of commonly used azanone donors and their characteristics, the overlapping molecular targets of HNO and NO are presented with an emphasis on heme models and proteins. We present also a brief description of metalloporphyrins and the main characteristics of their nitrosyl complexes, and then describe the reactivity of azanone towards Fe, Ru, Mn and Co porphyrins, briefly mentioning heme proteins, and focusing on 1HNO trapping and its discrimination from NO. A comparison of reaction kinetics and/or nitrosyl product stability with non-heme models is also described. We illustrate the promiscuity of iron porphyrins, the stabilization properties of Ru and the discriminating behavior of Mn and Co porphyrins, which allows the design of optical and electrochemical selective 1HNO sensors. Finally, a comparative analysis and future perspectives are presented, focusing on the in vivo reactivity of azanone and its putative endogenous production..